Analisis Kinerja Algoritma Hash dan MAC terhadap Integritas dan Autentikasi Data - Luthfiah Putri; Zulfa Khairunnisa; Junita Rahma Senjani; Septia Praramadani; Yulandari Hasibuan (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
In information systems, data security plays a crucial role, particularly in ensuring data integrity and authentication during storage and transmission processes. Hash algorithms and Message Authentication Codes (MAC) are two cryptographic techniques commonly employed for these purposes. Hash algorithms are primarily used to maintain data integrity, whereas MAC provides both data integrity and authentication through the use of a shared secret key. This study aims to analyze and compare the performance of hash algorithms and MAC in preserving data integrity and authentication. The research adopts a quantitative experimental method with a comparative analysis approach, using test data of varying sizes and evaluating performance based on specific operational parameters. The results indicate that hash algorithms are effective in detecting data modifications through hash value comparison, while MAC offers stronger guarantees by ensuring both data integrity and authentication using a shared secret key. These findings highlight the strengths and limitations of each mechanism and provide insights into their appropriate application in secure information systems. The findings further suggest that hash algorithms are more suitable for data integrity verification, whereas MAC is more appropriate for systems that require both data integrity and authentication simultaneously.